Exploring Iberian Peninsula Lamiaceae as Potential Therapeutic Approaches in Wound Healing - Mário P. Marques; Laura Mendonça; Beatriz G. Neves; Carla Varela; Paulo Oliveira; Célia Cabral (MDPI AG, 2023)
Skin tissue has a crucial role in protecting the human body from external harmful agents, preventing wounds that frequently demand proper healing approaches. The ethnobotanical knowledge of specific regions with further investigation on their medicinal plants has been paramount to create new and effective therapeutical agents, including for dermatological purposes. This review attempts, for the first time, to investigate the traditional applications of Lamiaceae medicinal plants that are already used by local communities in the Iberian Peninsula in wound healing. Henceforward, Iberian ethnobotanical surveys were reviewed, and the information about the traditional wound healing practices of Lamiaceae was comprehensively summarized. Afterwards, the scientific validation of each Lamiaceae species was exhaustively checked. From this, eight out of twenty-nine Lamiaceae medicinal plants were highlighted by their wound-related pharmacological evidence and are in-depth presented in this review. We suggest that future studies should focus on the isolation and identification of the active molecules of these Lamiaceae, followed by robust clinical trials that may confirm the security and effectiveness of such natural-based approaches. This will in turn pave the way for more reliable wound healing treatments.